2016
DOI: 10.2147/dddt.s80625
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the gastroprotective and anti-Helicobacter pylori activities of β-mangostin isolated from Cratoxylum arborescens (vahl) blume

Abstract: Purposeβ-Mangostin (BM) from Cratoxylum arborescens demonstrated various pharmacological activities such as anticancer and anti-inflammatory. In this study, we aimed to investigate its antiulcer activity against ethanol ulcer model in rats.Materials and methodsBM was isolated from C. arborescens. Gastric acid output, ulcer index, gross evaluation, mucus production, histological evaluation using hematoxylin and eosin and periodic acid–Schiff staining and immunohistochemical localization for heat shock protein 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 62 publications
1
12
0
3
Order By: Relevance
“…Cratoxylum arborescens (Vahl) Blume is widely distributed in Sabah and Sarawak (Malaysia) and its bark, roots and leaves are used in traditional medicine. Different xanthones, α-mangostin and β-mangostin have been isolated and identified from C. arborescens and have been studied as antiulcer protectors [ 84 ] and anti- H. pylori agents [ 83 , 84 ]. A study performed with α-mangostin showed that this compound (10 and 30 mg/kg) was able to protect gastric mucosa against ethanol-induced injury on rats, through exerting antioxidant protection, interfering with nitric oxide release, cyclooxygenases (COXs) inhibition and anti- H. pylori activity [ 84 ].…”
Section: Plant Products and Phytochemicals As Antiulcerogenic And mentioning
confidence: 99%
See 1 more Smart Citation
“…Cratoxylum arborescens (Vahl) Blume is widely distributed in Sabah and Sarawak (Malaysia) and its bark, roots and leaves are used in traditional medicine. Different xanthones, α-mangostin and β-mangostin have been isolated and identified from C. arborescens and have been studied as antiulcer protectors [ 84 ] and anti- H. pylori agents [ 83 , 84 ]. A study performed with α-mangostin showed that this compound (10 and 30 mg/kg) was able to protect gastric mucosa against ethanol-induced injury on rats, through exerting antioxidant protection, interfering with nitric oxide release, cyclooxygenases (COXs) inhibition and anti- H. pylori activity [ 84 ].…”
Section: Plant Products and Phytochemicals As Antiulcerogenic And mentioning
confidence: 99%
“…A study performed with α-mangostin showed that this compound (10 and 30 mg/kg) was able to protect gastric mucosa against ethanol-induced injury on rats, through exerting antioxidant protection, interfering with nitric oxide release, cyclooxygenases (COXs) inhibition and anti- H. pylori activity [ 84 ]. In another study, β-mangostin (5, 10 and 20 mg/kg) exhibited gastroprotective activity due to mucus production, anti-secretory, antioxidant, antiapoptotic and anti- H. pylori activity [ 83 ].…”
Section: Plant Products and Phytochemicals As Antiulcerogenic And mentioning
confidence: 99%
“…There are various noxious agents to the stomach resulting in mucosal ulceration, such as Helicobacter pylori infections, prolonged ingestion of nonsteroidal anti-inflammatory drugs (NAIDs), alcoholic drinks, psychological stress, and cigarette smoking. On the other hand, the stomach protects itself through many defense mechanisms, mainly adequate blood flow and bicarbonate and mucus secretions [ 149 ].…”
Section: Antiulcer Activity Of Propolismentioning
confidence: 99%
“…Histopathological scores indicated overall gastritis with damage to the surface epithelium, inflammatory cell infiltration, and submucosal edema, all of which were collectively found in the entire corpus and antrum region of mice. After measuring the degree of atrophic gastritis using the strategy used in previous studies [25,26], the grade of each tissue was recorded in terms of scores. Then, the sum of the detailed scores of each organization was calculated, followed by measuring the average score of each group; the scores were calculated by two different researchers to increase objectivity.…”
Section: Histological Evaluationmentioning
confidence: 99%